PENGARUH PERBEDAAN UMPAN PADA PANCING RAWAI TERHADAP HASIL TANGKAPAN IKAN SENANGIN (Eleutheronema tetradactylum), MENDAHARA ILIR - Egga Yolanda; Depison Depison; Lisna Lisna; Nurhayati Nurhayati; Darlim Darmawi; Fauzan Ramadan (Fakultas Perikanan dan Ilmu Kelautan, 2022)
East Tanjung Jabung Regency, Mendahara Ilir hamlet is a fishing base to the majority of longline fishing operations. The primary bait that used by fishermen in Mendahara Ilir is golden snails, but the golden snails are currently scarce, therefore is a need for alternative baits. Crustaceans are the primary food source for Senangin fish, the alternative baits utilized in this study were kapur shrimp and loreng shrimp. This study aimed to determine the effect of different types of bait on long line fishing gear on the catch of Senangin fish (Eleutheronema tetradactylum) in Mendahara Ilir. This study was carried out from December 5 to January 5, 2021, in the Mendahara Ilir waters. Experimental fishing was used as the research method, with a completely randomized design, 3 treatments, and 15 repetitions. The results showed that a lot of Senangin fish were caught on loreng shrimp bait of 61 fishes, kapur shrimp bait of 51 fishes, and golden Snail bait of 46 fishes. According to the findings of the analysis of variance, the capture with the golden snail bait was not statistically different from the catch with the kapur shrimp and loreng shrimp bait (P>0,05). The study's findings suggested that kapur shrimp and loreng shrimp bait can be employed as golden snail replacement baits.